2009
DOI: 10.1007/s10126-009-9181-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Selectively Bred Pacific Oyster Crassostrea gigas Families that Differ in Tolerance of Heat Shock

Abstract: Sessile inhabitants of marine intertidal environments commonly face heat stress, an important component of summer mortality syndrome in the Pacific oyster Crassostrea gigas. Marker-aided selection programs would be useful for developing oyster strains that resist summer mortality; however, there is currently a need to identify candidate genes associated with stress tolerance and to develop molecular markers associated with those genes. To identify candidate genes for further study, we used cDNA microarrays to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 98 publications
1
72
0
Order By: Relevance
“…Furthermore, correlating gene expression data with physiological and traditional life history parameters in response to chronic sub-lethal heat stress has become more prevalent. Such integrative approaches have been embraced across multiple disciplines and research interests, including freshwater (Doucet-Beaupré et al, 2010;Wang et al, 2012) and marine bivalves (Lang et al, 2009;Bettencourt et al, 2010;Clark et al, 2010;Craft et al, 2010;Fleury et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, correlating gene expression data with physiological and traditional life history parameters in response to chronic sub-lethal heat stress has become more prevalent. Such integrative approaches have been embraced across multiple disciplines and research interests, including freshwater (Doucet-Beaupré et al, 2010;Wang et al, 2012) and marine bivalves (Lang et al, 2009;Bettencourt et al, 2010;Clark et al, 2010;Craft et al, 2010;Fleury et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a related study of population divergence, Pespeni et al (2013) correlated gene expression to growth under common-garden conditions between northern and southern sea urchin populations (S. purpuratus) and found that population-level differences in growth were underlined by the differential expression of genes involved in protein synthesis and biomineralization. In Pacific oysters (Crassostrea gigas), Lang et al (2009) showed that transcriptional responses to heat stress varied between selectively bred families in aquaculture, whereas Chaney and Gracey (2011) identified a set of genes whose differential expression was correlated with future mass mortality events. These studies illustrate the power and applicability of transcriptomics to a diverse array of study systems and research questions.…”
Section: Introductionmentioning
confidence: 99%
“…The seawater is static during the treatment with salinity at 20 ppt and pH at 7.2. Previous studies indicate that 1 h thermal exposure is stressful to this species (Lang et al, 2009). The control group was maintained in ambient seawater (23 • ± 2 • C) throughout the study.…”
Section: Experimental Oysters and Thermal Stressmentioning
confidence: 82%
“…We chose to study gill tissue as it is a large organ with high surface area exposed to the environment and has been shown to be perturbed by thermal stress (Lang et al, 2009). Total RNA was extracted from gill suspensions using 1 mL TRIzol Reagent (Invitrogen, Carlsbad, CA) per 100 mg of tissue following the manufacturer's instructions.…”
Section: Samples Collection and Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation